Advances in vaccine-preventable diseases - Prof Helena Maltezou (International Journal of Infectious Diseases)
Introduction: Vaccine-preventable diseases (VPDs) remain a significant cause of morbidity and mortality in children. Methods: Recent advances in VPDs were reviewed. Results: A modelling study showed that vaccinations accounted for 40% of the reduction of infant mortality during 1974-2024. Measles vaccines accounted for most of the averted mortality the past 50 years. During 2000-2023 alone, measles deaths were reduced by 87%, while vaccination averted 60.3 million deaths globally. Regarding HPV vaccine, a US study showed a 62% drop in cervical cancer deaths in women <25 years over the last decade, which is mainly attributed to the HPV vaccines. From 2022, the WHO recommends 1-dose HPV vaccination schemes in low-income countries to surpass financial barriers. After the introduction of this schedule, 6 m more girls were vaccinated globally in 2023. Regarding RSV, a meta-analysis of trials of RSV vaccination during pregnancy found a risk ratio of 0.64 (95% CI: 0.43-0.96) of medically attended lower respiratory tract infections (LRTIs) in infants whose mothers were vaccinated and a risk ratio of 0.37 (95% CI: 0.18-0.79) of severe LRTIs in infants of vaccinated mothers. The effectiveness against LRTIs was documented at day 90, 120, 150 and 180 after birth and against severe LRTIs at day 90, 120 and 150 after birth. The study also showed that RSV vaccination during pregnancy is associated with a vaccine effectiveness (VE) against antimicrobial use of 16.9% (95% CI: 1.4-29.4%). The third topic concerned the efficacy and safety of the Butantan-dengue vaccine in children followed for a mean of 3.7 years. VE against any dengue serotype was 64.6% in 2-6 years children and 70.6% in 7-17 years old children. VE was higher in those with past infection. VE against severe dengue was 89%. No difference in vaccine safety was noted between vaccinated and control groups. The next study concerned the reduction in antibiotic use that occurred after the introduction of pneumococcus conjugate and the Haemophilus influenzae vaccines in the vaccination program in India in mid-2010 as well as future gains to 2028 if vaccination rates were to increase. The authors reported that a coverage similar to the coverage of DTP3 vaccine would avert 61.4% of attributable antibiotic use compared with 0%. It is also expected that 90% coverage would reduce health inequalities in antibiotic demand in this country. Regarding influenza vaccine, the US FDA approved the self- or caregiver-administration of the nasal spray influenza vaccine. Lastly, a large observational study from Italy found that COVID-19 vaccination was associated with lower risk of long-COVID at 3, 6, and 12 months after infection, particularly in adolescents. Discussion: In 2024 there have been considerable advances in major VPDs and vaccinations. Conclusion: This overview showed the current knowledge on vaccinations in children globally.